A atuação dos tutores nos processos de ensino e aprendizagem na EAD: ações de melhoria e orientação que impactam a aprendizagem discente - Velasques, Fransciély Valladas (2020)
Distance Education carries out the teaching and learning process through the Virtual Learning Environment that allows interaction between teachers, tutors and students. Thus, due to physical and temporal distance, there is a difficulty in engaging students in online disciplines, as in classroom teaching, considering the performance of activities, interaction in the environment, and especially active access to content. Thus, this research aims to identify what actions can be taken by tutors to ensure greater engagement and student learning in online disciplines. From these results, a manual was elaborated in which it presents these actions, contributing with the performance of the tutors and qualification of the teaching and learning processes. To contemplate the objective of the research, the investigative path was of a qualitative nature, based on the method of a single case study with incorporated units and content analysis based on previous categories. Thus, semi-structured interviews were conducted with teachers and tutors with experience in distance education from four institutions in southern Brazil, as well as online questionnaires were applied to students and graduates of these institutions. As a result, there are the main difficulties in the compression of technologies and organization of VLE, time management, understanding of the content, absence of face-to-face contact, in addition to the time to answer questions. As actions to qualify the learning process, it is suggested: the instrumentalization of the technological resources and organization of the VLE, tools for organizing time, audio and video tools, the help of tutors in teaching activities, synchronous communication for interaction and for immediate return, in addition to personalized monitoring by tutors to students.